Filmes de celulose incorporados com macro (K, Ca e Mg) e micronutrientes (Fe, Cu e Mn) como recipiente para propagação vegetal - Duarte, Maria Carolina Salomé (Universidade Federal de São Carlos, 2024)
An approach to minimizing the environmental, agronomic, and economic impacts of excessive fertilizer use is to optimize nutrient release through controlled and/or slow-release fertilizers, such as enhanced efficiency fertilizers (EEFs). However, many commercial EEFs contain non-biodegradable matrices that can lead to environmental contamination. Using biodegradable polymers like cellulose can mitigate this issue and improve fertilizer efficiency. In addition to functioning as EEFs, cellulose films can also serve as substrates for plant propagation, making them a promising alternative. This study developed and modified phosphorylated cellulose (P-Cel) films with phosphate groups to enhance the introduction and retention of ions such as K+, Mg 2+, Ca2+, Cu2+, Fe2+ e Mn2+. The films were prepared via casting with 1% (w/v) P-Cel incorporated with salts of Ca(NO3)2, KNO3, MgSO4.7H2O, CuSO4.5H2O, FeSO4.7H2O e MnSO4.H2O, and were characterized thermally (TGA, DSC), structurally (FTIR, XRD), and morphologically (SEM), in addition to evaluating ion release in water. The results indicate that the cellulose phosphorylation was successful, with 40% phosphorylation, and that the films functioned as EEFs, as confirmed by structural, thermal, and morphological analyses. The incorporation of salts was evidenced by band broadening and intensification and the appearance of new NO3-, SO42-, P=O, and P-O-H bands. XRD revealed interactions between the salts and P-Cel, particularly in equimolar quantities, while excess salt partially masked the characteristic peaks of P-Cel and the fertilizers. Thermal analyses confirmed the presence of salts, indicated by the release of water molecules from the hydrated salts after cation binding with phosphate. Elemental mapping (EDS) reinforced these interactions, showing a greater affinity of Ca2+ for PO43- compared to NO3-. Water solubility tests showed that macronutrients were released within the first 60 min, while micronutrients were released within 8 h, indicating a slower release than pure salts. Thus, P-Cel/fertilizer films demonstrate great potential as EEFs, as they are biodegradable, minimize environmental pollution, and provide controlled nutrient release, contributing to plant propagation and sustainability.
Cellulose films incorporated with macro- (K, Ca, and Mg) and micronutrients (Fe, Cu, and Mn) as a container for plant propagation.
Keywords: Filmes; Fertilizantes; Micronutrientes e macronutrientes; Celulose; Films; Fertilizers; Micronutrients and macronutrients; Cellulose; CIENCIAS EXATAS E DA TERRA::QUIMICA; 12. Consumo e Produção Responsáveis